2020
DOI: 10.31234/osf.io/bu58f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How do recall requirements affect decision-making in free recall initiation? A linear ballistic accumulator approach

Abstract: Models of free recall describe free recall initiation as a decision-making process in which items compete to be retrieved. Recently, Osth and Farrell (2019) applied evidence accumulation models to complete RT distributions and serial positions of participants’ first recalls in free recall which resulted in some novel conclusions about primacy and recency effects. Specifically, the results of the modeling favored an account in which primacy was due to reinstatement of the start-of-the-list and recency was found… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In models such as the temporal context model (TCM; Howard & Kahana, 2002) and the Osth and Dennis (2015) model, changes in context produce an exponential relationship between the similarity of the current context and the stored context. However, decades of research have found that the forgetting curves for recognition and other memory tasks are best described by a power function (Anderson & Schooler, 1991;Deffenbacher et al, 2008;Donkin & Nosofsky, 2012a;Rubin & Wenzel, 1996;Wickelgren, 1974Wickelgren, , 1975Wixted & Ebbesen, 1991, but see Osth & Farrell, 2019and Osth et al, 2021, for exceptions in free recall tasks). A solution to this is to assume that context elements drift at different rates (Howard et al, 2015;Mozer et al, 2009).…”
Section: Visual Schematic Of Context Driftmentioning
confidence: 99%
“…In models such as the temporal context model (TCM; Howard & Kahana, 2002) and the Osth and Dennis (2015) model, changes in context produce an exponential relationship between the similarity of the current context and the stored context. However, decades of research have found that the forgetting curves for recognition and other memory tasks are best described by a power function (Anderson & Schooler, 1991;Deffenbacher et al, 2008;Donkin & Nosofsky, 2012a;Rubin & Wenzel, 1996;Wickelgren, 1974Wickelgren, , 1975Wixted & Ebbesen, 1991, but see Osth & Farrell, 2019and Osth et al, 2021, for exceptions in free recall tasks). A solution to this is to assume that context elements drift at different rates (Howard et al, 2015;Mozer et al, 2009).…”
Section: Visual Schematic Of Context Driftmentioning
confidence: 99%